Structural and Luminescence Properties in Dy3+ Doped Antimony Strontium-Magnesium-Oxyfluroborate Glasses (Bulletin of Pure and Applied Sciences – Physics, 2020)
A series of glasses by melting quenching method fabricated for spectroscopic  investigations of Dysprosium (Dy3+) particle ions deposited on Antimony (Sb) - Magnesium (Mg) - Strontium (Sr) Oxyfluoroborate (BSbMgfSr) glasses. The  structural and optical characterizations such as XRD, UV-VIS-NIR absorption  spectroscopy, photoluminescence (PL) (excitation and emission) were accomplished  to study the properties of prepared glasses. The transitions from lowest energy state  to an excited state in RE3+ ions were identified using optical UV-NIR absorption  spectra. By the use of Judd-Ofelt theory the J-O intensity parameters Ωλ (λ = 2, 4, 6)  have been evaluated utilizing the absorption spectra with the determination of  experimental (fexp) and calculated (fcal) oscillator strengths. The emission of light from  glass system was concluded through PL spectra (Excitation and emission) for  Dy3+ion. The radiative properties resembling radiative transition probability (AR),  radiative-lifetime (τR), and branching-ratio (β) of the glasses have also estimated.  Stimulated emission cross-section (σse) of the glasses also calculated for the feasibility  of lasing applications. Experimental lifetime (τexp) of the decay curves of the  BSbMgfSrD glasses were also calculated upon excitation by suitable wavelengths of  all various concentrations of the RE3+ ions.